2001
DOI: 10.1023/a:1010225117654
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cachaça (aguardente) is a rum-style spirit made from sugar cane juice by artisanal methods in Brazil. A study was made of the production, biochemistry and microbiology of the process in fifteen distilleries in Sul de Minas. Identification of 443 yeasts showed Saccharomyces cerevisiae to be the predominant yeast but Rhodotorula glutinis and Candida maltosa were predominant in three cases. Bacterial infection is a potential problem, particularly in older wooden vats, when the ratio of yeasts:bacteria can be 10:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Acetoin is also related to the biosynthesis of 2,3-butanediol and diacetil [35]. Saccharomyces strains generally do not produce signiWcant amounts of acetoin, which is a characteristic of Kloeckera and Hanseniaspora yeasts [10,36]. Similar results to these were published by Valles et al [40], who found higher concentrations of acetoin in cider that was fermented indigenously.…”
Section: Chemical Analyses During Fermentationsupporting
confidence: 59%
See 2 more Smart Citations
“…Acetoin is also related to the biosynthesis of 2,3-butanediol and diacetil [35]. Saccharomyces strains generally do not produce signiWcant amounts of acetoin, which is a characteristic of Kloeckera and Hanseniaspora yeasts [10,36]. Similar results to these were published by Valles et al [40], who found higher concentrations of acetoin in cider that was fermented indigenously.…”
Section: Chemical Analyses During Fermentationsupporting
confidence: 59%
“…Alcohols (ethanol and glycerol), organic acids (acetic acid, lactic acid, malic acid, succinic acid, tartaric acid, and citric acid), and carbohydrates (glucose, sucrose, and fructose) were obtained from pulp extracts and analyzed [36]. Analyses were carried out with a high-performance liquid chromatography system (HPLC) (Shimadzu, model LC-10Ai (Shimadzu Corp., Tokyo, Japan), equipped with a dual detection system consisting of a UV detector and a refractive index detector (RID-10A SPD-10Ai).…”
Section: Substrates and Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors can influence the quality of distilled alcoholic beverages; however, the identity of yeasts and the fermentation conditions are the most important determinants of flavour, since the majority of flavour compounds are formed during fermentation (Oliveira et al 2005;Dato et al 2005). There are many genera and species of yeast in sugar cane juice, but species of the genus Saccharomyces are mainly responsible for the alcoholic fermentation (Schwan et al 2001;González et al 2007) and Saccharomyces cerevisiae is the predominant species during spontaneous fermentation for the production of cachaça (Schwan et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohols, carbohydrates and organic acids were quantified by high-performance liquid chromatography (HPLC) using adapted methodology of Schwan et al (2001), in Shimadzu LC-10Ai chromatograph, SCR-101H Shimpack column (Shimadzu). Carbohydrates and alcohols were detected by refractive index (RID-10A detector) at 30 °C and the organic acids by the ultraviolet detector (SPD-10Ai) at 210 nm at 50 °C, both using the perchloric acid mobile phase at 100 mM, 0.6 mL min -1 flow.…”
Section: Characterization and Quantification Of Alcohols Carbohydratmentioning
confidence: 99%